Propuesta de un sistema de gestión ambiental basado en la norma ISO 14001:2015 para la lavandería y tintorería Dayantex - Masaquiza Ramirez, Lisbeth Ananitay (2022)
Worldwide, textile industries generate many environmental impacts, in special due to the use of dyes, colorants, solvents, and other chemicals which are used in the washing and dyeing processes. This research allowed to design a proposal about an environmental management system for the laundry and dry cleaning DAYANTEX in Pelileo, allowing to set preventive measures, control and mitigation of environmental impacts and accomplish the demanded requirements by the ISO 14001:2015 standard. As a first fundamental step, a diagnostic was applied to know the situation in which the company is, where each one of the processes were identified as well as environmental aspects and impacts, in addition, the environmental legal requirements that apply to the activities in the organization were determined. Subsequently, the most significant components were evaluated, and the degree of compliance was rated based on current legal requirements. Based on the results of the initial phase, the matrix of environmental aspects and impacts also the current legal regulations, the company´s environmental policy was proposed, and environmental programs were created with their respective objectives, goals and action plans around the significant components, which will allow to prevent, mitigate and / or control the environmental impacts of the organization. Finally, the environmental management System manual was prepared with the procedures that the ISO 14001:2015 standard requires as part of the SGA.